Identifier Management and Resolution: Conforming the IEEE Standard for Learning Object Metadata - Godoy, Roberto Javier (2008)
Uniform Resource Identifiers are an integral part of the current Architecture of the World Wide Web. This work analyzes the implications and possibilities of using Universal Resource Names as unique and persistent identifiers in systems for management of decentralized content and federated collections. Particularly, discussion focuses on applying such identifiers on the context of a learning object repository that the authors are developing at Universidad Nacional del Litoral, according to the IEEE 1484.12.1 standard for Learning Object Metadata. It is explained why Uniform Resource Locators are inadequate, and why Universal Resource Names are preferable. A standardized resolution service over Hypertext Transfer Protocol is recommended for locating resources, and usage of Uniform Resource Characteristics for accessing Learning Object Metadata is proposed. Finally, a content-negotiation mechanism for selecting the best representation among several format or language variants is outlined. The proposed naming schema provides a doubleindirection mechanism, comparable to the Human- Friendly Names approach proposed by Ballintijn, van Steen, and Tanenbaum for improving scalability and usability in naming replicated resources.